MULTISPECIES FISH PASSAGE BEHAVIOUR IN A VERTICAL SLOT FISHWAY ON THE RICHELIEU RIVER, QUEBEC, CANADA. (10th January 2012) - Thiem, J. D.; Binder, T. R.; Dumont, P.; Hatin, D.; Hatry, C.; Katopodis, C.; Stamplecoskie, K. M.; Cooke, S. J.
ABSTRACT A shift from target species to ecosystem restoration has generated interest in developing fishways that are capable of passing entire fish communities. Although a number of multispecies fishways now exist in North America, evaluations of these fishways are lacking. We used a passive integrated transponder antenna array to quantify passage success and passage duration of fish using a vertical slot fishway (85 m in length, 2.65 m elevation rise, 12 regular pools and 2 turning basins) at a low head dam on the Richelieu River in Quebec, Canada. Fourteen of the 18 tagged species re‐ascended the fishway, and passage efficiency was highly variable among species (range 25%–100%); however, it was >50% for five of the species well represented in this study (n > 10) (Atlantic salmon, channel catfish, smallmouth bass, walleye and white sucker). Passage duration was likewise highly variable both among and within species (e.g. 1.0–452.9 h for smallmouth bass, 2.4–237.5 h for shorthead redhorse). Although this fishway design was not uniformly successful in passing fish of all species, this study does reveal the species that have problems with ascent and provides an estimate on the time spent in the fishway that is an important component of passage delay. Such information could be used to inform future design refinements to facilitate passage of the entire assemblage with minimal delay. Copyright © 2012 John Wiley & Sons, Ltd.